The environment and redshift dependence of accretion on to dark matter haloes and subhaloes - Tillson, H; Miller, L; Devriendt, J (2011)
A dark-matter-only Horizon Project simulation is used to investigate the environment and redshift dependences of accretion on to both haloes and subhaloes. These objects grow in the simulation via mergers and via accretion of diffuse non-halo material, and we measure the combined signal from these two modes of accretion. It is found that the halo accretion rate varies less strongly with redshift than predicted by the Extended Press-Schechter formalism and is dominated by minor merger and diffuse accretion events at z= 0, for all haloes. These latter growth mechanisms may be able to drive the radio-mode feedback hypothesised for recent galaxy-formation models, and have both the correct accretion rate and the form of cosmological evolution. The low-redshift subhalo accretors in the simulation form a mass-selected subsample safely above the mass resolution limit that reside in the outer regions of their host, with ∼70 per cent beyond their host's virial radius, where they are probably not being significantly stripped of mass. These subhaloes accrete, on average, at higher rates than haloes at low redshift and we argue that this is due to their enhanced clustering at small scales. At cluster scales, the mass accretion rate on to haloes and subhaloes at low redshift is found to be only weakly dependent on environment, and we confirm that at z∼ 2 haloes accrete independently of their environment at all scales, as reported by other authors. By comparing our results with an observational study of black hole growth, we support previous suggestions that at z > 1, dark matter haloes and their associated central black holes grew coevally, but show that by the present-day, dark matter haloes could be accreting at fractional rates that are up to a factor of 3 - 4 higher than their associated black holes. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.